The physical education of girls are in generaleducational establishments of western Volyn in 1921–1939 - Гук [Guk О.], Олексій (Slobozhanskyi Herald of Science and Sport, 2012)
The historical aspects of development of physical culture of girls in general establishments of Western Volyn in an intermilitary period which is pre-condition of creation of the new system of physical education are presented in the article. It is well-proven that the system of physical education of students, and in particular girls, functioned in two basic directions – within the limits of general schools and of out-of-school time. Participating of girls is exposed in sporting sections and mugs and the role of public educationally-sporting societies of Volhynia is shown in development of physical education of girls of school age on the basis of scientific sources, archived data, programs of the Ukrainian magazines.